SOSIALISASI PENERAPAN PROTOKOL KESEHATAN PADA MASA PANDEMI COVID-19 DI MAGUWOHARJO DAN SOSIALISASI DAMPAK PENGGUNAAN KANTONG PPLASTIK SEKALI PAKAI DI DESA SUMBEREJO, SLEMAN, JAWA TENGAH - Stephanie Astrid Ayu (UPPM Politeknik Gorontalo, 2021)
Maguwoharjo village and Sumberejo village are residential areas in Central Java province that fall into the densely populated category. The condition of most of the population in the area is quite fulfilled in terms of economy. Current pandemic conditions affect the daily habits and routines of citizens at the location of community service. The majority of Maguwoharjo villagers have not realized the maximum importance of maintaining and implementing health protocols (including 3M, using masks, washing hands with soap, and maintaining distance) as one of the efforts of residents to help government programs in suppressing the rate of spread of the Covid-19 virus. While the condition of the majority of sumberejo villagers, is a community group that has not fully understood the negative impact of the accumulation of single-use plastic waste that is often used by housewives and other residents in everyday life. Based on the problems outlined above, this community service work program focuses on the implementation of education for maguwoharjo villagers about the importance of implementing health protocols in everyday life and providing education to the community in Sumberejo Village about the negative impact of single-use plastic bag use that causes more and more plastic waste.